PENGARUH MODEL PEMBELAJARAN GROUP TO GROUP EXCHANGE BERBANTUAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 INDRALAYA - Helen Rahayu; Siti Fatimah; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This study discusses about the effect of learning model of Group To Group with the worksheet of learners on students' learning outcomes on economic subjects in SMA Negeri 1 Indralaya. The formulation of the research problem is "is there any influence of learning model of Group To Group Exchange in the Education Worksheet Worksheet to the learning outcomes on economic subjects in SMA Negeri 1 Indralaya?". The research was conducted in SMA Negeri 1 Indralaya by using research type of experimental design with One Group Pretest-Posttest Design research design. Population in this research is all X IPS in SMA Negeri 1 Indralaya. The sample used Cluster Random Sampling technique, so selected X class IPS 1 as experiment class which amounted to 31 students. Data collection techniques used in this research are observation and test. Hypothesis uses parametric statistic that is product moment correlation and thitung ≥ t table. The results obtained t value of 14.31 which means thitung> ttable ie 14.31> 1.670 then the hypothesis Ho rejected and Ha accepted. So it can be concluded there is influence of learning model Group To Group Exchange assisted Sheets of learners learners on the results of learners on economic subjects in SMA Negeri 1 Indralaya. The obstacles in this study when applying the model of learning Group To Group Exchange is when the division of groups of learners less regular in positioning their seats because the division of the group is divided randomly and exchange seats.